Accounting Information Systems (AIS) and knowledge management : a case study - Muhamad Sori, Zulkarnain (EuroJournals Publishing, 2009)
This study seeks to examine the use of Accounting Information Systems (AIS) by ZBMS Sdn. Bhd., and it’s contribution to the knowledge management and strategic role of the organisation. ZBMS is a company that registered in Kuala Lumpur and operate inconstruction industry. The company used automated AIS known as ‘Contract Plus –Financial & Project Accounting’ package commercially developed by a private company(ZYXW). Wide variety of people that involve in the company’s operation within and outside the organisation uses accounting information generated by this system for decision-making. Based on input provided by operational level managers, the Contract Plus software produces monthly projects’ income statements, balance sheets and statement of changes in financial position for the strategic and tactical managers to plan, control and make decision on the resources allocation. The role-played by AIS enhanced the organisations’ accountingfunctions, and add information value. The automated AIS speed up the process to generatefinancial statements and overcome human weaknesses in data processing. The systemenhances management of resources and the process of monitoring, control and prediction ofZBMS business for better future. With the advent of AIS, the growth of tacit and explicit knowledge could be seen from the intensive training of personnel at the early stage of system implementation to the development and use of company’s own manual in training of new staff and assisting the job of existing staff. Given the benefit of AIS to ZBMS, this paper recommended that the source of data should be fully automated, and the existing system should be upgraded through computerise the pre-tendering and post-tendering of projects to enable AIS integration.